2001
DOI: 10.1002/jnr.1183
|View full text |Cite
|
Sign up to set email alerts
|

17β‐estradiol inhibits cytokine, chemokine, and chemokine receptor mRNA expression in the central nervous system of female mice with experimental autoimmune encephalomyelitis

Abstract: Cytokines and chemokines govern leukocyte trafficking, thus regulating inflammatory responses. In this study, the anti-inflammatory effects of low dose 17 beta-estradiol were evaluated on chemokine, chemokine receptor, and cytokine expression in the spinal cords (SC) of BV8S2 transgenic female mice during acute and recovery phases of experimental autoimmune encephalomyelitis (EAE). In EAE protected mice, 17 beta-estradiol strongly inhibited mRNA expression of the chemokines RANTES, MIP-1 alpha, MIP-2, IP-10, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 55 publications
(51 reference statements)
9
79
0
2
Order By: Relevance
“…Castration of male mice worsens EAE in males (17), whereas ovariectomy does not have a major impact on this disease in female mice (18,19). Such observations suggest that it is the higher level of androgens in males that is protecting this sex from EAE development.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Castration of male mice worsens EAE in males (17), whereas ovariectomy does not have a major impact on this disease in female mice (18,19). Such observations suggest that it is the higher level of androgens in males that is protecting this sex from EAE development.…”
Section: Resultsmentioning
confidence: 94%
“…Castration of male mice worsens EAE (17), whereas ovariectomy does not have a major impact on disease (18,19), suggesting that the higher androgen levels in males protects this sex from developing autoimmunity. Regarding possible mediators of these androgen effects, we previously identified that that the nuclear receptor peroxisome proliferator activated receptor (PPAR)α is expressed at higher levels by male vs. female T cells and appears to control T-cell proliferation and Th1 cytokine production uniquely in male mice (20).…”
mentioning
confidence: 99%
“…Physiological or pharmacological fluctuations in estrogen levels have been recognised since a long time to play a regulatory role in EAE ( [13,108,111,119,150]). Oral administration of low doses of estrogenic hormones, 17beta-estradiol and ethinyl estradiol, drastically reduce the severity of EAE and this effect was reconciled with a decrease in the production of inflammatory Th1 cytokines (such as inteferon-c (IFN-c), Tumor Necrosis Factor-a (TNF-a), Interleukin (IL)-1 and IL-6), chemokines/receptors, while increasing the expression of anti-inflammatory Th2 cytokines (including IL-4, IL-5 and Transforming Growth factor-b3 (TGF-b3)) ( [13,108,150,222]).…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…Oral administration of low doses of estrogenic hormones, 17beta-estradiol and ethinyl estradiol, drastically reduce the severity of EAE and this effect was reconciled with a decrease in the production of inflammatory Th1 cytokines (such as inteferon-c (IFN-c), Tumor Necrosis Factor-a (TNF-a), Interleukin (IL)-1 and IL-6), chemokines/receptors, while increasing the expression of anti-inflammatory Th2 cytokines (including IL-4, IL-5 and Transforming Growth factor-b3 (TGF-b3)) ( [13,108,150,222]). This observation together with the fact that no infiltrating lymphocytes were found in the hormone-treated animals, led to the conclusion that estrogens protects mice from EAE by inhibiting the recruitment of T cells and macrophages into the CNS.…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…In one of the most typical of these studies, experimental autoimmune encephalomyelitis was induced in mice, and estradiol and ethynil estradiol were administered to investigate the effect of estrogens on neurons (15). This and other related studies have shown that estrogens decrease the production of tumor necrosis factor-α (TNF α) and other chemokines (15,16), inhibit major histocompatibility complex-II (MHC-II) expression (17), and protect dendritic cells from inflammation (18). After the administration of estrogens in the study, the decrease in the production of TNF-α, interferon gamma (IFN-gamma), and interleukin-12 (IL-12) in dendritic cells; the decrease in antigen presentation to T cells (19); and a shift from T helper-1 (TH-1) to T helper-2 (TH-2) cells were observed (19).…”
Section: Ms Sex Steroids Hormonal Contraceptive Methodsmentioning
confidence: 99%